Determinants of The Effectiveness Of Implementation Performance Based-Budgeting and Budget Absorption in Local Governments - Rita Friyani; Riski Hernando (Faculty of Economics, Universitas Sriwijaya, 2019)
This study aims to try to examine the influence of Local Government Employee Understanding, Training, and External Pressure (Determinants) on the Effectiveness of Implementation Performance-Based Budgeting and Budget Absorption in Local Governments (Study on Jambi City Government). The population is all Dinas and SKPD in Jambi City Government. The sampling technique uses a purposive sampling approach. The criteria used are those involved in performance-based budgeting and budget execution practices. So, that the total sampel used was 60 people. Data were obtained by questionnaire distribution techniques to respondents throughout the Dinas and SKPD in Jambi City Government. Data analysis using SEM PLS. The results of data processing found that training, understanding, education and external pressure had a positive effect on the effectiveness of performance-based budget implementation and budget absorption.